Distinguishing characteristics of the doctorate programs in business administration in Colombia: The student perspective (2019)
Purpose: The purpose of this paper is to focus on achieving an approximation to the understanding of the situation of management doctoral programs in Colombia. Despite the need to evaluate the suitability and relevance of management doctoral programs, at present, there are no studies that inquire about the conditions of students and graduates of doctoral programs in the management research field. Design/methodology/approach: An exploratory exercise was developed, information was collected with students and graduates of various doctoral programs to initiate a contextualization and characterization in terms of doctoral training from the students’ point of view. Findings: At the end, conclusions are presented on the status and prospects to continue with future studies that allow find the conditions of doctoral level training in the management field and the impact of the research carried out by doctoral students and graduates of these programs. Originality/value: This paper will contribute to the review of the existing studies regarding doctoral education in management in Colombia, which presents principal motivations about investigation in the field of study, and as such, open the space to question about the reality of the programs in terms of those who are receiving the formation. © 2019, Emerald Publishing Limited.